RESPON HASIL 2 VARIETAS TANAMAN KACANG TANAH (Arachis hypogaea L.) DALAM PENGAPLIKASIAN PGPR AKAR PUTRI MALU (Mimosa pudica L.) - Tria Indah Safitri; Christa Dyah Utami; Liliek Dwi Soelaksini; Andarula Galushasti (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2026)
The cause of the decline in peanut production is due to insufficient nutrients in the soil. The solution is to use PGPR (plant growth promoting rhizobacteria) biofertilizer from the roots of the sensitive plant, which contains a group of bacteria that can improve the availability of nitrogen and phosphate. In addition, the use of superior varieties is also an important factor in increasing peanut yields. The objective is to measure the concentration of PGPR in mimosa root that is suitable for increasing the yield of two peanut varieties. The implementation will take place from July to December 2025 in Patemon Village, Pakusari District, Jember Regency, East Java. A factorial randomized block design (RAK) with two treatment factors will be applied. The first factor is the peanut variety, namely: Katana 2 and Tala 1 varieties, while the second factor is the concentration of PGPR in mimosa pudica roots, namely: PGPR 0 ml/l (Control), PGPR 25 ml/l, PGPR 50 ml/l, and PGPR 75 ml/l. The results showed that the variety had a significant effect on the parameters of the number of pods and the weight of 100 seeds. In the treatment of PGPR root hair, the best concentration was PGPR 25 ml/l, which had a significant effect on the parameters of wet pod weight per plot and the weight of 100 seeds. Meanwhile, the interaction between the variety and PGPR showed no effect on all observation parameters.